EQUITY RISK PREMIUM PADA INDUSTRI PERBANKAN - Harjito, Yunus; Hapsari, Dian Indriana (BISNIS, 2016)
This study aims to examine the factors that influence the equityrisk premium in the banking industry are listed on the Indonesia Stock Exchange. The samples used were 23 banking industry for 2010-2014. Five variables proposed that auditor tenure, earnings quality, leverage, beta, and earnings per share to detect whether there is an influence on the equity risk premium. Equity risk premium is desired reward investors to generate income is not fixed in relation to the equity share hers. So far the equity risk premium is often described as the most important value in finance and investment. Analysis of the data used in this research is multiple linear regression with the hopeto obtain a comprehensive picture of the influence of variables auditor tenure, earnings quality, leverage, beta, and earning per share of the equity risk premium by using SPSS version 21 for Windows. The results showed that the auditor tenure, earnings quality, and earnings per share significantly affect the equity risk premium. But two other variables (leverage and beta) proved no effect on the equity risk premium.